SEJARAH PERKEMBANGAN HUKUM ISLAM (PERIODE KHULAFAURRASYIDIN PADA MASA UMAR BIN KHATTAB) - Ali Akbar; Era Majida Daulay; Rahma Yani; Saidin Ali Hutapea; Muhammad Ilham Hadi (STKIP Subang, 2024)
The development of Islamic law has existed for a long time, one of which was during the time of Caliph Umar bin Khattab ra. During Umar's time, he established the judiciary as the front guard in progress and development, as evidenced by the appointment of qodi (judges), the salaries of judges and employees, all of which were based on the Koran, Sunnah, ijtima' friends and ijtihad. Apart from that, there were still many legal developments that emerged during Umar's time, for example the issue of the limit on cutting off hands for thieves. Cut off one of his legs and don't cut off his hand, because with that one hand he can still use it for eating and for praying. Legal issues regarding adultery, divorce, etc.